Embedded software verification and debugging - Lettnin, Djones; Winterholer, Markus (Embedded systems (Springer (Firm)), 2017)
This book provides comprehensive coverage of verification and debugging techniques for the embedded software frequently used in safety-critical applications (e.g., automotive), where failures are unacceptable. It also discusses emerging trends and techniques.- Resumé vydavatel